Modern Forecasting Models in Action: Improving Macroeconomic Analyses at Central Banks - Malin Adolfson; Michael K. Andersson; Jesper Lindé; Mattias Villani; Anders Vredin (Sveriges Riksbank, 2005)
There are many indications that formal methods are not used to their full potential by central banks today. In this paper we demonstrate how BVAR and DSGE models can be used to shed light on questions that policy makers deal with in practice using data from Sweden. We compare the forecast performance of BVAR and DSGE models with the Riksbank's official, more subjective forecasts, both in terms of the actual forecasts and root mean square errors. We also discuss how to combine model- and judgment based forecasts, and show that the combined forecast performs well out-of-sample. In addition, we show the advantages of structural analysis and use the models for interpreting the recent development of the inflation rate using historical decompositions. Lastly, we discuss the monetary transmission mechanism in the formal models, using impulse response functions and conditional forecasts.
Keywords: E37; E47; E52; 330; Bayesian inference; Combined forecasts; DSGE models; Forecasting; Monetary policy; Subjective forecasting; Vector autoregressions